PENGEMBANGAN EKONOMI PESANTREN BERBASIS KEARIFAN LOKAL - Riadi, Luthfi; Febrianto, Achmad; Saifuddin, Saifuddin (JURNAL ISLAM NUSANTARA, 2021)
This study discusses the economic development of Islamic boarding schools in Probolinggo Regency by empowering coastal Muslim communities by producing marine processed products. Islamic boarding schools have provided a new nuance for coastal communities in the form of economic improvement. The researcher uses a qualitative phenomenological method with data collection techniques, namely observation and interviews and several references obtained from reputable books and journals related to empowerment and economic development. The results showed that; 1) The efforts made by the Nurul Jadid Islamic Boarding School in formulating a pattern of empowering coastal communities are based on two approaches, namely increasing the ability of the community independently and creating opportunities for economic development for the community; 2) Economic development of coastal communities is carried out through strengthening the social structure, economic equity, education on the values of economic independence, community participation, and community involvement in regional development.